Eco-Friendly Synthesis of Pyrrolo[1,2-A] Quinoline Derivatives and Evaluating Their Effects On Hypertension, Inflammation, And Docking Studies: Pharmaceutical sciences- Chemistry - Patil, Pramod; Padmashal, Basavaraj; Uppar, Vijayakumar; H, Pavankumar (International Journal of Life Science and Pharma Research, 2023)
Chronic inflammation diseases are a major cause of death worldwide, including heart diseases, kidney diseases, and liverdiseases. Researchers are working on developing effective anti-inflammatory drugs. COX-2 inhibitors like coxibs were developed toreduce gastrointestinal side effects but were later withdrawn due to cardiovascular events. The need for safer coxibs and a betterunderstanding of COX-1 and COX-2 in cardiovascular diseases and stroke is necessary. Chronic inflammation can last for months oryears, and its effects vary depending on the underlying cause and the body's ability to repair damage. On the other hand, hypertension isa major cause of global mortality, mortality for 12.8% of annual deaths. The number of adults with hypertension has almost doubled to1.28 billion, with the greatest increase in low- and middle-income countries, particularly sub-Saharan Africa, where 120 million people mayhave hypertension. This poses a significant challenge for the region in therapeutic development. In this study, by an eco-friendly method,we have synthesized pyrrolo[1,2-a]quinoline derivatives for anti-inflammatory activity along with its molecular docking and antihypertension activity. Green chemistry in organic synthesis has become a major focus in recent decades, to develop more environmentallyfriendly methods. Green chemistry has a significant focus in organic synthesis over the past few decades. Two key principles are "safersolvents" and "energy efficiency” reducing hazardous solvents, and minimizing energy consumption. The synthesis of pyrrolo[1,2-a]quinoline derivatives was obtained by a one-pot reaction in which 4-methylquinoline was treated with substituent phenacyl bromidesand two different alkynes respectively, in the presence of TEA (triethylamine) with the addition of a minimal amount of acetonitrile as asolvent. The moieties 2a, 3b, and 3a showed the highest inhibitory capacity against reference standard ibuprofen in anti-inflammatoryactivity, along with their molecular docking study of these compounds displayed better (-3.5) to good (-9.2) docking score within thebinding pocket towards crystal structure derivative. Derivative 3b has shown significant inhibition at 100 µg in anti-hypertensive activity.